Factor affecting the integration of Arabic CALL into the IIUM Arabic language curriculum - Ahmed, Ibrahim (2002)
During this era of ever-emerging technological advances, it is necessary to expose students to the use of the computer in the classroom in order to ensure that they may benefit from interacting with the most up-to-date teaching aids (Ahmed, 2002,p.3). Of the several factors that encourage the use of CALL in the classroom, students’ positive attitudes and responses to the novelty and fun of the new software programmes is a major one; that student independence is encouraged is another. Equally, however, there are factors working against the use of CALL. These include budget restrictions, the attitude of university authorities towards supporting teachers who wish to use such technology (especially as it relates to the provision of re-training opportunities), and personal factors such as a teacher’s fear when faced with something new and unknown.